2018
DOI: 10.14720/aas.2018.111.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Content of bioactive compounds and antioxidant activity in garlic (Allium sativum L.)

Abstract: Garlic (Allium sativum L.) is highly regarded throughout the world for both its medicinal and culinary properties. With its bioactive compounds and sulphur containing compounds, high trace mineral content, garlic has shown anti-viral, antibacterial, anti-fungal and antioxidant abilities. This work has focused on the measurement and comparison of the total polyphenols content, the total sulphur content and antioxidant activity of the studied varieties of garlic in the area of Nitra and Bardejov, Slovak Republic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Garlic skin and straw are characterized by their high contents of phenolic compounds. The total polyphenol (extracted by ethanol) contents of garlic powder, skin and straw reportedly range from 0.43 to 0.64, 12.88 to 16.74 and 6.36 to 12.40 mg/g fresh weight (FW), respectively ( Kahyaoğlu, 2021 ; Micová et al., 2018 ); similar results were reported by Drszczyk et al., 2019 . Garlic powder contains approximately 0.36% (DM basis) oil ( Zou and He, 2020 ).…”
Section: Chemical Composition and Bioactive Compounds Of Garlic Productsmentioning
confidence: 54%
See 1 more Smart Citation
“…Garlic skin and straw are characterized by their high contents of phenolic compounds. The total polyphenol (extracted by ethanol) contents of garlic powder, skin and straw reportedly range from 0.43 to 0.64, 12.88 to 16.74 and 6.36 to 12.40 mg/g fresh weight (FW), respectively ( Kahyaoğlu, 2021 ; Micová et al., 2018 ); similar results were reported by Drszczyk et al., 2019 . Garlic powder contains approximately 0.36% (DM basis) oil ( Zou and He, 2020 ).…”
Section: Chemical Composition and Bioactive Compounds Of Garlic Productsmentioning
confidence: 54%
“…In terms of the bioactive compounds of garlic products, fresh or dried garlic bulbs are rich in organosulphur compounds. One study found that the total content of organosulphur compounds in garlic powder ranged from 0.56% to 0.80% on a DM basis ( Micová et al., 2018 ). Alliin is the main active component of these organosulphur compounds, comprising more than 90% of the total organosulphur compounds in garlic powder; alliin is the precursor of allicin ( Zhai et al., 2018 ).…”
Section: Chemical Composition and Bioactive Compounds Of Garlic Productsmentioning
confidence: 99%
“…Subsequently, onion has a flavonoids content of quercetin conjugation that can retain its stability up to the temperature of 100 °C. At the same time, the total polyphenol of garlic extract in ethanol ranged from 559 mg kg -1 to 763 mg kg -1 (Micova et al, 2018).…”
Section: Antioxidant Activitymentioning
confidence: 95%
“…Allicin, ajoene, diallyl trisulfide (DATS), diallyl disulfide (DADS), and diallyl sulfide (DAS) are oil-soluble organosulfur compounds that give garlic its pungent odor . Garlic has a 0.56% sulfur content compared to its original weight …”
Section: Major Chemical Constituents Of Garlicmentioning
confidence: 99%
“…20 Garlic has a 0.56% sulfur content compared to its original weight. 21 The main sulfur compounds are alliin (S-allylcysteine sulfoxide) and others such as γ-glutamyl-S-trans-1-propenylcysteine, and γ-glutamyl-S-allyl-L-cysteine (GSAC) in raw intact or dehydrated garlic. The main sulfur compound, alliin, is present in raw garlic bulbs and in garlic powder, which has 8 g of sulfur per kg of garlic.…”
Section: Major Chemical Constituents Of Garlicmentioning
confidence: 99%